Heat and mass transfer analysis of tea particles in low-temperature spray dryers using a combination of swirl and Co-current flows - Henry Carles; Eflita Yohana; Mohammad Tauviqirrahman; Ridho; Mohamad Djaeni; Mohamad Endy Yulianto; Kwang-Hwan Choi (Case Studies in Thermal Engineering)
Tea solutions contains antioxidants in the form of catechins which sensitive to heat. This study explores combining co-current and swirl flow patterns within the drying chamber to achieve efficient, low-temperature drying processes. The research uses Computational Fluid Dynamics (CFD) to study heat and mass transfer characteristics in a spray dryer, focusing on different flow compositions of swirl and co-current flows at ratios of 25 %:75 %, 50 %:50 %, and 75 %:25 %. This research also examines variations in hot air inlet temperature (80 °C, 70 °C, and 60 °C). Key parameters, including temperature and mass fractions of water and water vapor, serve as indicators for evaluating transfer efficiency. Findings indicate configurations with a predominant swirl flow of 75 % at 80 °C yield the most favorable outcomes, with a significant temperature drop of 34.141 °C and 93.59 % evaporation of H2O(l) particles. Conversely, configurations with a predominant co-current flow of 75 % exhibit lower efficiency, with a temperature decrease of 29.599 °C and 84.80 % evaporation of H2O(l) particles.